Comportamento mecânico de uma cerâmica Y-TZP após desgaste com broca diamantada e degradação hidrotérmica - Guilardi, Luís Felipe (2016)
This study aimed to determine the effects of grinding and low temperature aging on the surface micromorphology (roughness measurement, Scanning Electron Microscopy and Atomic Force Microscopy), phase transformation (t→m), biaxial flexural strength and structural reliability (Weibull analysis) of an yttrium-stabilized tetragonal zirconia polycrystalline ceramic. One hundred and eighty ceramic discs (15.0 × 1.2 ± 0.2 mm, VITA In-Ceram YZ) were prepared and randomly assigned into six groups according to 2 factors (n = 30): grinding (Ctrl without treatment, as-sintered; Xfine grinding with extra fine diamond bur - 30 μm; Coarse grinding by coarse diamond bur - 151 μm), and aging (without or with aging: CtrlLTD; XfineLTD; CoarseLTD). Grinding was performed in an oscillatory motion with a contra-angle handpiece under constant water-cooling. Low temperature degradation (LTD) was simulated in an autoclave at 134 °C, under 2 bar pressure, for 20 h. The roughness (Ra and Rz parameters) significantly increased after grinding in accordance with bur grit-size (Coarse > Xfine > Ctrl), and aging promoted distinct effects (Ctrl = CtrlLTD; Xfine > XfineLTD; Coarse = CoarseLTD). Grinding increased the m-phase, and aging led to an increase in the m-phase in all groups. However, different susceptibilities to LTD were observed. Weibull analysis showed a significant increase in the characteristic strength after grinding (Coarse = Xfine > Ctrl), while aging did not lead to any deleterious impact. Neither grinding nor aging resulted in any deleterious impact (no statistical decrease in the Weibull moduli) on material reliability. Thus, neither grinding nor aging led to a deleterious effect on the mechanical properties of the evaluated Y-TZP ceramic although a high m-phase content and roughness were observed.